2012
DOI: 10.1242/jcs.096396
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Endoplasmic Reticulum Localization of Gp78 Ubiquitin Ligase Activity

Abstract: SummaryGp78 (also known as AMFR and RNF45) is an E3 ubiquitin ligase that targets proteins for proteasomal degradation through endoplasmic reticulum (ER)-associated degradation (ERAD). In this study, we showed that gp78-mediated ubiquitylation is initiated in the peripheral ER. Substrate monoubiquitylation and gp78 CUE domain integrity restricted substrate to the peripheral ER, where CUE domain interactions and polyubiquitylation reduced gp78 mobility. Derlin-1 and derlin-2, which are involved in the retrotran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…1C). Similarly, co-transfection of FlagGp78wt with mutated HA-tagged ubiquitin (K29R, K48R and K63R, denoted HA-Ubmono), preventing Gp78-dependent polyubiquitin chain elongation (St-Pierre et al, 2012), results in longer and AMF-insensitive coupling times (Fig. 1C).…”
Section: Results and Discussion Amf-gp78 Regulation Of Er-mitochondrimentioning
confidence: 90%
See 2 more Smart Citations
“…1C). Similarly, co-transfection of FlagGp78wt with mutated HA-tagged ubiquitin (K29R, K48R and K63R, denoted HA-Ubmono), preventing Gp78-dependent polyubiquitin chain elongation (St-Pierre et al, 2012), results in longer and AMF-insensitive coupling times (Fig. 1C).…”
Section: Results and Discussion Amf-gp78 Regulation Of Er-mitochondrimentioning
confidence: 90%
“…To study Gp78-mediated regulation of ER-mitochondria interaction by electron microscopy, we stably transfected HT-1080 fibrosarcoma cells, which express elevated levels of endogenous Gp78 (St-Pierre et al, 2012;Tsai et al, 2007), with doxycyclininducible Gp78 short hairpin RNA (shRNA; shGp78). 3D confocal analysis showed that shGp78 knockdown reduced syntaxin-17 overlap with mitochondria ( Fig.…”
Section: Amf-gp78 Selectively Regulate Rer-mitochondria Contactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doxycyclin inducible Gp78-targeted shRNA lentiviral vectors incorporating two shRNAs (sh2 and sh6) that effectively targeted Gp78 (St-Pierre et al, 2012) were used to generate Gp78 knockdown HT-1080 cells. Doxycyclin treatment resulted in reduced Gp78 expression by western blot that was generally more pronounced in sh6 transfected cells ( Fig.…”
Section: Dynamin-dependent Internalization Of Amf Downregulates Its Cmentioning
confidence: 99%
“…Gp78 internalizes AMF via a noncaveolar, dynamin-and PI3K-dependent raft-mediated endocytic pathway to the smooth ER (Benlimame et al, 1998;Kojic et al, 2007;Kojic et al, 2008;Le et al, 2002;Le and Nabi, 2003). We recently localized the initiation of Gp78-dependent substrate ubiquitylation to the peripheral smooth ER domain (St-Pierre et al, 2012). However, the relationship between the raftdependent endocytosis of AMF, its signaling and Gp78 function in ERAD remains unknown.…”
Section: Introductionmentioning
confidence: 99%